Role of different Culicoides vectors (Diptera: Ceratopogonidae) in bluetongue virus transmission and overwintering in Sardinia (Italy). Issue 1 (December 2016) - Foxi, Cipriano; Delrio, Gavino; Falchi, Giovanni; Marche, Maria; Satta, Giuseppe; Ruiu, Luca
Abstract Background Bluetongue (BT) epidemics have affected the Mediterranean island of Sardinia since 2000. WhileCulicoides imicola represents the main bluetongue virus (BTV) vector, other EuropeanCulicoides biting midges, possibly implicated in virus transmission, have been detected here. Understanding their distribution, seasonal abundance, and infection rates is necessary to predict disease incidence and spread across coastal and inland areas, and to define their role in virus overwintering. Methods Biting midge abundance was determined by light traps on selected farms representing diverse climatic conditions of Sardinia. Livestock-associatedCulicoides species were morphologically and molecularly identified. Infection rates in prevailing midge species captured in 2013 during a BTV-1 outbreak were determined using RT-qPCR based virus detection in insect body pools, supplemented by specific body region analyses. The seasonal infection prevalence inCulicoides samples collected in 2001 in a BTV-2 affected farm was also determined. Results The Newsteadi complex (C. newsteadi species A and species B) prevailed among all biting midge species (47.7 %), followed byC. imicola (27.8 %) and the Obsoletus complex (C. obsoletus andC. scoticus ) (17.6 %). WhilstCulicoides imicola was more abundant along the coast, the Newsteadi complex was frequently collected at higher altitude and the Obsoletus complex was notably associated to cattle farms.Culicoides pulicaris andC. punctatus abundance was found to be marginal in all farms. BTV was detected in parous female samples of all these species, and the full dissemination of the virus within the body ofC. imicola, C. obsoletus, C. scoticus, and Newsteadi complex species was confirmed by analyses of thorax and head, containing salivary glands. Higher infection rates were associated withC. scoticus, C. newsteadi species A and species B, compared toC. imicola . The virus was detected inC. newsteadi species A andC. obsoletus in winter and spring, whereas it was mainly found in summer and autumn inC. imicola . Conclusions In Sardinia, bluetongue virus is transmitted by multipleCulicoides vectors, includingC. imicola and the Newsteadi complex being the most important. The Newsteadi complex and other midge species can play an important role in internal areas and are likely to be directly involved in virus overwintering.